PTEN inhibitor attenuates cardiac fibrosis by regulating the M2 macrophage phenotype via the PI3K/AKT/TGF-β/Smad 2/3 signaling pathway. (1st June 2022) - Zhuang, Chenchen; Guo, Ziyi; Zhu, Jumo; Wang, Wenjuan; Sun, Runmin; Qi, Miaomiao; Wang, Qiongying; Fan, Xin; Ma, Runxin; Yu, Jing
Abstract: Cardiac fibrosis is a key feature of hypertensive cardiac remodeling. In response to microenvironmental stimuli, phenotypic and functional changes in macrophages are considered important determinants of cardiac fibrosis attenuation. VO-OHpic, a phosphatase and tension homolog of chromosome 10 (PTEN) inhibitor, has been demonstrated to be cardioprotective in cardiac remodeling. However, whether VO-OHpic can improve cardiac fibrosis and macrophage polarization remains elusive. The interaction between VO-OHpic and the macrophage phenotype to attenuate cardiac fibrosis was studied in both spontaneously hypertensive rats in vivo and an Ang II-induced hypertension model in vitro . In vitro experiments showed that VO-OHpic promoted M2 macrophage polarization and markedly inhibited proinflammatory M1 macrophages, while VO-OHpic treatment of protein kinase B (AKT)-knockdown/LY294002 (a PI3K inhibitor) macrophages exerted a reduced effect. In a coculture system, culturing cardiac fibroblasts with VO-OHpic-treated macrophages led to significant suppression of proliferation, fibrotic marker expression, and transforming growth factor (TGF)-β and Smad 2/3 protein expression. Taken together, VO-OHpic mediated a fibro-protective effect and increased M2 macrophage polarization via the phosphatidylinositol 3-kinase (PI3K)/AKT/TGF-β/Smad2/3 pathway. Highlights: VO-OHpic suppresses pro-inflammation M1 macrophages and activates anti-inflammatory M2 macrophages. VO-OHpic ameliorates cardiac fibrosis by regulating macrophage phenotype. The PI3K/AKT/TGF-β/Smad 2/3 pathway plays a critical role in the relationship between VO-OHpic and macrophage phenotype on cardiac fibrosis.